Digital innovation and entrepreneurship - Whittington, Richard, 1958- (Cambridge University Press, 2018)
The digital economy encompasses more than half the world, and in today's business market, those with a technology background have an advantage. This textbook provides students who already have digital expertise with a solid foundation in business and entrepreneurship in order to launch and run a business. Using a logical, objective-based structure, the book guides students to a comprehensive and practical understanding of innovation and entrepreneurship. Chapters progress through the steps in creating a successful digital business: framing the business, promotion and sales, delivery and operations, value capture, growth and scalability, intellectual property and protection, and leadership and structure. Features include: learning objectives, introductions, conclusions, tables and figures, highlighted key terms, and analysis and design exercises in each chapter; a wide range of real-world examples; a rolling case study of a hypothetical digital business that models the concepts covered in each chapter; appendices of business terms, including those relating to product licensing, customer service agreements and customer delivery contracts; and key terms explained throughout. Supplemen